Null and Overt Subjects in the Acquisition of Modern Standard Arabic as a First Language by Bilingual Moroccan Children - Халід Лахбібі; Мохамед Йоу (Психолінгвістика, 2024)
Goal. In Modern Standard Arabic (MSA), the subject can be null or overt, occurring preverbally (VSO) and postverbally (SVO). The current acquisitional study presents results from picture description task with 24 Moroccan child learners of MSA (aging between 5;1 and 9;1). Further, it explores the extent to which learners employ the economy principle in their acquisition of null and overt subjects, and what structure is preferably produced by children.